Strata Conference Santa Clara 2012 : complete video compilation. (O'Reilly Media, 2012)
"The future clearly belongs to those who understand how to collect and use their data successfully, and the time to get started is now. At the Strata Conference, people from tech, marketing, and many other fields gathered to learn the latest skills, tools, and technologies for making a data-driven business work. This video compilation offers you a front row seat for every tutorial, session, and keynote at the conference."--Resource description page.